Parvulastra exigua in South Africa: one species or more? - Payne, Robyn P (Department of Biological Sciences, 2014)
Parvulastra exigua is a widely distributed and prominent member of the temperate intertidal fauna in the southern hemisphere, occurring along the southern coastline of Africa, southeastern Australia and several oceanic islands. In South Africa, it is found in sympatry with the endemic Parvulastra dyscrita and the two are differentiated predominantly by gonopore placement. P. exigua gives rise to distinct lecithotrophic benthic larvae that hatch from sticky egg masses laid via oral gonopores. In contrast, P. dyscrita has aboral gonopores that release eggs into the water column, from which pelagic larvae hatch. Several recent studies have suggested that there is a cryptic species of P. exigua in South Africa, based on genetic evidence or the differential placement of the gonopores. A morphological, anatomical and genetic investigation was performed on a total collection of 346 P. exigua and 8 P. dyscrita specimens from the east and west coast of South Africa, with the hope of confirming whether cryptic species and/or P. exigua specimens with aboral gonopores are present in the population and determining if they correlate. Neither the cryptic species, nor P. exigua specimens with aboral gonopores were obtained. This study tentatively refutes the claim of the existence of aboral gonopores in the South African P. exigua population, and the distinction between P. exigua and P. dyscrita is confirmed, with features separating these two species clarified.